Persepsi Masyarakat Desa Wukirsari dan Girirejo Terhadap Eksistensi Cagar Alam Imogiri Berdasarkan Studi Demografis - Dalitbang, Bidang; Anisah Qurrotu Aini; Anasya Zabna Sabilla; Kotimah; Winda Lutfiana Hafidz; Nur Surantiwi (Jurnal Riset Daerah, 2025)
The Imogiri Nature Reserve area is located between two villages, namely Wukirsari Village and Girirejo Village, which are included in the Imogiri Kapanewon area, Bantul Regency. The community around the Imogiri Nature Reserve area plays an important role in the sustainability of the area. This study aims to determine the views of the community around the Imogiri Nature Reserve regarding the impact on the sustainability of community life based on community characteristics such as gender, age, education level and occupation. This study uses a survey method using questionnaires and direct interviews with the people of Wukirsari and Girirejo Villages. The results of the study indicate that people at certain levels of demographic have different significant influences on each aspect including the status of the area, benefits of the area, and management of the Imogiri Nature Reserve area. Based on the research that has been conducted, it is concluded that the 28-37 year age group has a dominant negative perception, while positive perceptions are more common in the 58-70 year age group. At the last level of education, Elementary School and Junior High School have doubtful perceptions, while at the last level of education, No School, Senior High School, and College have moderate perceptions. The results based on the type of work showed that the entrepreneur group, Housewives (IRT), self-employed, and Civil Servants (PNS) have a positive level of perception, while in the community with the type of work of servants and students have a less positive level of perception. Meanwhile, the results obtained on the level of community perception based on gender showed that on average, women have a positive level of perception. Meanwhile, men have a less positive level of perception.